2014
DOI: 10.3892/ijmm.2014.1968
|View full text |Cite
|
Sign up to set email alerts
|

ZnPP reduces autophagy and induces apoptosis, thus aggravating liver ischemia/reperfusion injury in vitro

Abstract: Abstract. There is growing evidence indicating that autophagy plays a protective role in liver ischemia/reperfusion (IR) injury. Heme oxygenase-1 (HO-1) can also prevent liver IR injury by limiting inflammation and inducing an anti-apoptotic response. Autophagy also plays a crucial role in liver IR injury. The aim of the present study was to investigate the role of HO-1 in liver IR injury and the association between HO-1, autophagy and apoptotic pathways. IR simulation was performed using buffalo rat liver (BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…In this sense, our results (Figures B) clearly show that RSV strongly downregulated HO‐1 protein content, and this correlates with the anti‐autophagic effect of RSV. Consistent with our results, it has been shown that the HO‐1 inhibitor zinc protoporphyrin strongly inhibits autophagy and induces apoptosis and that HO‐1 induces protective autophagy …”
Section: Discussionsupporting
confidence: 92%
“…In this sense, our results (Figures B) clearly show that RSV strongly downregulated HO‐1 protein content, and this correlates with the anti‐autophagic effect of RSV. Consistent with our results, it has been shown that the HO‐1 inhibitor zinc protoporphyrin strongly inhibits autophagy and induces apoptosis and that HO‐1 induces protective autophagy …”
Section: Discussionsupporting
confidence: 92%
“…A study using human lymphoblastoid cells demonstrated that GEM can incorporate into the DNA and inhibit DNA synthesis, 77 inducing DNA damage response and degradation of PARP1 via autophagy. 80 In summary, our results indicate that the combination of GEM and AgNPs synergistically induces apoptosis in A2780 cells via DNA fragmentation.…”
Section: Gem and Agnps Induce Apoptosismentioning
confidence: 92%
“…Both Hemin and ZnPP may produce other side effects. However, according to the recent study, Hemin has been shown safely and effectively enhance the HO-1 expression [ 18 ] and ZnPP also recommended as an inhibitor of HO-1 for relative few off-targets effect [ 19 ] and the validity of ZnPP has been checked in our previous study [ 20 ]. Because there were no differences in any of the parameters between ZnPP- and hemin-treated rats in the sham groups, the results of groups (sham + Hemin) and (sham + ZnPP) were pooled and were referred to as sham.…”
Section: Methodsmentioning
confidence: 99%